Workshop Perhitungan dan Pelaporan PPh 21 melalui DJP Online - Herlambang, Rinaldi Sri; Hutomo, Dany Prio; Suprayoga, Adi; Zulkifli, Suripto Moh.; Wisin, Muhammad Saddam; Putri, Nurahmelia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The Directorate General of Taxes continues to strive to issue various policies to motivate taxpayers to report and calculate taxes independently, DGT provides convenience to taxpayers without having to come and fill out tax returns manually. This workshop will discuss how participants know how to calculate and report PPh 21 tax through DGT Online. The phenomenon is that there are still many taxpayers who do not know about tax calculation and reporting, so many ignore their obligations because they are considered troublesome. Through this workshop, it is hoped that taxpayers will comply with the Tax Law. The workshop method is in the form of providing material as well as training where participants not only get material but are also given the opportunity to practice calculating taxes directly. The place for the implementation of community service in the Campus Hall of STIE Ekadharma Indonesia Bekasi, which was attended by 93 participants consisting of 39 participants from grade 12 students who already have KTPs, 54 participants from the general public who have working status. Based on the results of the questionnaire, 50.5% of the participants stated that the workshop material was very clear and the participants understood how to use DGT Online. So it can be concluded that the workshop activities help participants to understand and implement how to report Income Tax 21 correctly.